An update on the therapeutic implications of long-chain acyl-coenzyme A synthetases in nervous system diseases - Wu, Zhimin; Sun, Jun; Liao, Zhi; Qiao, Jia; Chen, Chuan; Ling, Cong; Wang, Hui (Frontiers in Neuroscience, 2022)
Long-chain acyl-coenzyme A synthetases (ACSLs) are a family of CoA synthetases that activate fatty acid (FA) with chain lengths of 12–20 carbon atoms by forming the acyl-AMP derivative in an isozyme-specific manner. This family mainly includes five members (ACSL1, ACSL3, ACSL4, ACSL5, and ACSL6), which are thought to have specific and different functions in FA metabolism and oxidative stress of mammals. Accumulating evidence shows that the dysfunction of ACSLs is likely to affect cell proliferation and lead to metabolic diseases in multiple organs and systems through different signaling pathways and molecular mechanisms. Hence, a central theme of this review is to emphasize the therapeutic implications of ACSLs in nervous system disorders.